The Influence of Business Ethics and Diversity on ESG Disclosure: Empirical Evidence from Indonesian Firms - Subaki , Achmad; ., Tukirin (Journal of Ecohumanism, 2024)
This study examines the impact of corporate governance mechanisms, board characteristics, and ethical leadership on Environmental, Social, and Governance (ESG) performance in Indonesian companies. The analysis investigates how board ethics, independence, tenure, ownership structure, and other governance factors influence ESG scores. The findings reveal that board ethics and independence significantly improve ESG performance, supporting the role of ethical leadership and resource dependence theory in shaping corporate sustainability. Additionally, the study highlights the role of institutional ownership in driving ESG outcomes, particularly in emerging markets. Cultural factors, such as board culture, also contribute to the variability in ESG performance, suggesting the importance of aligning corporate governance practices with local values and global sustainability standards. The results have important theoretical implications, extending corporate governance theories to the context of developing economies. Practically, the findings provide insights for policymakers, corporate leaders, and investors to enhance ESG performance through effective governance reforms and ethical leadership. This study offers a significant contribution to the growing literature on ESG in emerging markets and provides a foundation for future research on corporate sustainability in different institutional settings.